Manipulation mechanisms of bubble aggregation and evolution in inertial cavitation fields - Rui Liu; Jing Hu; Yaorong Wu; Shi Chen; Chenghui Wang; Runyang Mo; Jianzhong Guo; Shuyu Lin (Ultrasonics Sonochemistry)
Spherical bubble clusters was observed at 28 kHz and 40 kHz, and the evolution of the clusters was investigated. It was found that the cluster was dense when it located at the antinode of standing waves, while it became sparse when it deviates from the antinode, and the bifurcation of period doubling was observed in this nonlinear bubble system. In clusters, there exists complex fragmentation and coalescence, implying a bubble transportation cycle inside the clusters, which may enhance the interaction between the cluster and surrounding tiny bubbles. With the decreasing of acoustic pressure, the cluster spreads out gradually. A theoretical model is developed to explore the attractive effects of the cluster on surrounding bubbles, where the high hydrostatic pressure environments was considered, with the aim of providing a mechanism for the manipulation of cavitation field. It is very different by comparing the equilibrium radii distribution of the repulsive zone at 28 kHz and 600 kHz. At high hydrostatic pressure, it is possible to obtain a much denser cluster, which attracts bubbles within 2 mm of the surrounding region. As a result, it was found the key factors to affect the interactions are the ratio of acoustic pressure to hydrostatic pressure, hydrostatic pressure, and acoustic frequency. Our theoretical predictions can provide support for optimizing the cavitation behavior of bubble populations at high hydrostatic pressures.